Association of adult attachment with delays in accessing specialist care in women with ovarian cancer. Issue 4 (4th July 2022) - Datta, Soumitra Shankar; Fraser, Lindsay; Burnell, Matthew; Nasreen, Shazia; Ghosh, Manisha; Ojha, Aparupa; Saha, Tania; Mukhopadhyay, Asima; Lanceley, Anne; Menon, Usha
ABSTRACT: Objective: Advanced stage at diagnosis and delayed presentation are common in ovarian cancer (OC). The objective of the current study was to explore the association of adult attachment pattern with delays in accessing specialist oncology care in patients with OC. Methods: A cross-sectional structured interview study of patients with OC presenting to an Indian cancer center was undertaken. Consenting patients completed Experiences of Close Relationships–Relationship Style questionnaire (ECR-RS) and Medical Outcome Survey–Social Support Survey (MOS–SSS). Multivariate linear regression with "time to presentation to cancer specialist" as the dependent variable was undertaken. Results: In all, 132 of 155 (85%) patients with OC who were invited were interviewed. An increased ECR-RS attachment anxiety score ( P  = .01) and being part of a multigenerational extended household ( P  = .04) were both independently associated with delay in presentation to a cancer specialist. There was no association between delay in presentation and social support. Conclusions: Among patients with OC, adult attachment may contribute to delays in presentation. It may be important for the cancer symptom awareness efforts in primary care to include educating physicians on recognizing and interacting with patients with insecure attachment styles. The association of delays in presentation for women with OC living in multigenerational extended households needs more indepth exploration. Supplemental data for this article is available online at https://doi.org/10.1080/07347332.2022.2025510 .